A Low-Cost Multiplatform VLC System Prototype for Indoor Attocell Downlink Communication - Nascimento, Alaf; Costa, Wesley; Camporez, Higor; Zwaag, Klaas; Santos, Francisco; Silva, Jair (Anais do Workshop de Computação Urbana (CoUrb); 2026: Anais do X Workshop de Computação Urbana, 2026)
Devices operating in the Radio Frequency (RF) spectrum face capacity limitations due to licensed bandwidth and rapidly growing connectivity demand. Visible Light Communication (VLC) emerges as a complementary alternative, leveraging existing lighting infrastructure for energy-efficient indoor communication. However, for widespread adoption, VLC devices must achieve a cost comparable to established technologies. This work proposes a Plug-and-Play (PnP) USB dongle for VLC data reception based on low-cost hardware, along with a multiplatform interface for reactive data visualization. Our prototype achieves error-free downlink communication in attocell scenarios over distances up to 280 cm under line-of-sight (LOS) conditions.